Carpal Tunnel Syndrome Risk: Impact of Work Duration on Farmers - Roestijawati, Nendyah; Fakih, Mohammad; Yuliani, Massita Dwi; Firinda, Rizma Haidif; Dafaulhaq, Ahmad Fawwaz (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Farmers, as an informal work group, are at high risk of occupational diseases, including Carpal Tunnel Syndrome (CTS). This study analyzes the relationship between work duration and suspected CTS incidence among farmers in Linggasari Village, Kembaran District, Banyumas Regency.An observational study was conducted on 72 farmers using interview methods, physical examinations, and CTS provocation tests. Data were analyzed bivariately using Chi-Square statistical testing. Of 72 respondents, 26 (36.11%) were suspected of having CTS, with 16 (61.54%) having work duration exceeding 52,320 hours. Among 46 respondents not suspected of CTS, 13 (28.26%) had work duration less than 52,230 hours. Statistical analysis revealed a p-value of 0.006 (p < 0.05), indicating a significant relationship between work duration and suspected CTS incidence. A statistically significant correlation exists between work duration and suspected CTS among farmers.